2015
DOI: 10.1089/ars.2014.5942
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nrf2 Polymorphism Haplotypes with Acute Lung Injury Phenotypes in Inbred Strains of Mice

Abstract: Aims: Nrf2 is a master transcription factor for antioxidant response element (ARE)-mediated cytoprotective gene induction. A protective role for pulmonary Nrf2 was determined in model oxidative disorders, including hyperoxia-induced acute lung injury (ALI). To obtain additional insights into the function and genetic regulation of Nrf2, we assessed functional single nucleotide polymorphisms (SNPs) of Nrf2 in inbred mouse strains and tested whether sequence variation is associated with hyperoxia susceptibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…Nrf2 antioxidant responses occur after exposure to other liver toxins including aflatoxin (Kensler et al 2014; Merrick et al 2012; Singh et al 2015) and carbon tetrachloride (Chen et al 2014), and are found in other organ toxicities including in the lung (Cho et al 2015) and nasal cavity (Dunnick et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 antioxidant responses occur after exposure to other liver toxins including aflatoxin (Kensler et al 2014; Merrick et al 2012; Singh et al 2015) and carbon tetrachloride (Chen et al 2014), and are found in other organ toxicities including in the lung (Cho et al 2015) and nasal cavity (Dunnick et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the expression of intra and extracellular antioxidants in airway epithelial cells and fluids is prominent. Numerous in vitro and in vivo studies have demonstrated the importance of Nrf2 activation to decrease oxidative stress and inflammation in conditions such as pulmonary fibrosis, cystic fibrosis, emphysema, COPD, ALI, asthma, bronchopulmonary dysplasia, and airway infections (Cho, Kleeberger 2015; Chan, Kan 1999). In the particular context of ALI/ARDS, the benefits of both basal and induced Nrf2 signaling have been investigated in various cellular and mouse models, as well as in human patient samples, as will be discussed below.…”
Section: The Protective Role Of Nrf2 In Alimentioning
confidence: 99%
“…2015a; Cordova et al 2011; Cho et al 2015c). In a hyperoxia-induced ALI mouse model, the functional effects of promoter and coding SNPs revealed that some haplotypes characteristic to certain inbred mouse strains confer increased susceptibility to hyperoxia due to lower Nrf2 mRNA expression and compromised protein function (Cho et al 2015a). These studies will help identify populations at greater risk of developing ALI that would benefit from more effective chemopreventive interventions through Nrf2 upregulation.…”
Section: The Protective Role Of Nrf2 In Alimentioning
confidence: 99%
See 1 more Smart Citation
“…The Nrf2 polymorphism contributes to poor prognosis in cancers, including cholangiocarcinoma [65], lung cancer [66], and breast cancer [67]. It also contributed to diseases, such as increasing the risk of acute lung injury [68,69] as well as blood pressure and cardiovascular mortality in patients with hemodialysis [70].…”
Section: Nrf2 Activation In Tumorsmentioning
confidence: 99%